O olhar da curiosidade : um diálogo entre os espaços não formais e alunos do ensino fundamental - Oliveira, Andreza Rayane Holanda Reis de (2018)
Non-Formal Spaces as places suitable for learning of students of different age groups, have been discussed in several papers in the form of articles, reports and dissertations. This research aimed to understand the perceptions of students in Non-Formal Spaces from the “curious look” of primary school students. For that, four Non-Formal Spaces were visited in the city of Manaus - AM: Forest of Science, Amazonian Museum, Mindu Municipal Park and CIGS Zoo. In these places were followed 16 students of elementary school from different schools in the city of Manaus. It was used as methodology to analyze the data, Grounded Theory, aiming at the elaboration of an explanatory theory to investigate what elementary students learn in these spaces. In order to arrive at the substantive theory in question, the following steps were followed: Initially the interviews with the students were made and later transcribed. After transcription of the interviews, the coding was followed (open, axial and selective). It was decided to use the open coding of the line-by-line type, in which the first codes were assigned to the interviews. At the end of the open coding a great amount of data was verified, that needed to be regrouped by means of the axial codification. It was also in the axial coding that the emergent subcategories were created, that later were represented by hierarchical relations. In the selective coding, following the paradigmatic model proposed by Strauss and Corbin (2008) the central category of the research, “Learning the way of life of the animals”, that represented the phenomenon, and the other analytical categories was evidenced: “Concerning school appraisals”, representing the causal conditions; “Complementing what they saw in the NonFormal Spaces with the contents studied in the school”, that represented the intervening condition; “Using visual memory to remember animals”, representing actions/interactions; and “Discovering the variety of fauna”, which represented the consequences. In view of this analysis, it was verified that the students are concerned with the content studied in the NonFormal Spaces, since they attribute importance to the school evaluations. In addition to emphasizing that memorizing the image of the animals and the class, in general, in the NFE will make them pass the tests, know matter and can answer the questions in the textbook. It was also verified that the affective or appreciative learning predominated in the Non-Formal Spaces classes for the elementary students who were interviewed. Keywords: Non-Formal Spaces; Grounded Theory; Student Perceptions